2022
DOI: 10.3390/jcm11195691
|View full text |Cite
|
Sign up to set email alerts
|

Gut as an Alternative Entry Route for SARS-CoV-2: Current Evidence and Uncertainties of Productive Enteric Infection in COVID-19

Abstract: The gut has been proposed as a potential alternative entry route for SARS-CoV-2. This was mainly based on the high levels of SARS-CoV-2 receptor expressed in the gastrointestinal (GI) tract, the observations of GI disorders (such as diarrhea) in some COVID-19 patients and the detection of SARS-CoV-2 RNA in feces. However, the underlying mechanisms remain poorly understood. It has been proposed that SARS-CoV-2 can productively infect enterocytes, damaging the intestinal barrier and contributing to inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 187 publications
(285 reference statements)
0
19
0
Order By: Relevance
“…Differentiation of Caco-2 cells to M-like cells can be induced by co-culture with Raji cells and is relevant for nanoparticles uptake in related intestinal models (Cabellos et al, 2017). The gut has been suggested as an alternative entry site of SARS-CoV-2 and may be infected both directly or by systemic spread of the virus from the lung and other organs (Clerbaux et al, 2022; Guo et al, 2021). Thus, we challenged the gut epithelium model with the virus from both the top and the bottom.…”
Section: Resultsmentioning
confidence: 99%
“…Differentiation of Caco-2 cells to M-like cells can be induced by co-culture with Raji cells and is relevant for nanoparticles uptake in related intestinal models (Cabellos et al, 2017). The gut has been suggested as an alternative entry site of SARS-CoV-2 and may be infected both directly or by systemic spread of the virus from the lung and other organs (Clerbaux et al, 2022; Guo et al, 2021). Thus, we challenged the gut epithelium model with the virus from both the top and the bottom.…”
Section: Resultsmentioning
confidence: 99%
“…The four workshop reports published for externals or circulated internally ( 14 , 25 ) were conceived as ways of sharing the progress of the project within the CIAO community and with a wider audience following the workshops. At first, the authorship was restricted to members of the coordination group.…”
Section: Resultsmentioning
confidence: 99%
“…Immunomodulator use was associated with a higher risk of anxiety [ 6 ]. Clerbaux et al performed a literature review and found that SARS-CoV-2 could induce intestinal inflammation by binding to ACE2 and infecting intestinal bacteria [ 7 , 8 ]. In addition, Serban et al and Łykowska-Szuber et al examined the literature to show the relationships between acute mesenteric ischemia and deranged liver tests among hospitalized COVID-19 patients [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%